Thermal evolution of the intracratonic Paris Basin: Insights from 3D basin modelling. (September 2020) - Torelli, Martina; Traby, Renaud; Teles, Vanessa; Ducros, Mathieu
Abstract: The thermal evolution of the Paris Basin (PB) has been widely studied using 1D, 2D and, more rarely, 3D thermal models. It is well documented that the PB experienced higher temperatures in the past compared to what is currently observed. However, a quantitative analysis of the main processes and parameters that affect the temperature distribution, at the basin scale and over time, is still not available. In this study, through basin modeling which accounts for the main processes of the thermal evolution of sedimentary basins, we analyze and quantify the role of the different geological mechanisms by discriminating the causes of abnormal temperatures during the Late Mesozoic. This is done with a 3D basin model built from base Moho to present-day topography using the TemisFlow® basin modelling software. The model includes thermal processes within an evolving upper crust defined by three main structural domains. Each crustal sector presents radiogenic heat production, conductivity and thickness values which are used as input parameters to reproduce the paleo- and present-day basal heat flow variations observed in the basin. The model calculates heat flow through time in both, crust and sedimentary column where the crust is coupled with the geological evolution of the basin. This approach allows estimating the eroded thickness during the main Tertiary uplift event and therefore the maximum temperature in the Late Cretaceous. The model is constrained by different types of paleo-thermo-chronometers and by 52 wells that are regionally distributed over the entire basin, resulting in a new regional thermal history of the PB. The amount of missing section in the Cretaceous chalk which mainly affected the eastern part of the basin is increased by up to 500m compared with previous studies and constitutes the key controlling factor of the temperature evolution. This new regional thermal history of the Paris Basin may be important for further analysis of the HC generation from the Lower Jurassic Toarcian source-rock and bring new insights into the geothermal potential of the basin. Highlights: Thermal evolution of the Paris basin constrained on well temperatures and paleo-thermometers. 3D basin model including lithospheric processes for better constrained thermal conditions. Comparison of the different mechanisms that affected the thermal evolution of the Paris basin. Cretaceous chalk deposition played a major on the thermal evolution of the Paris basin. Assessment of the duration, distribution and thickness of the Upper Cretaceous erosion.